2022
DOI: 10.3390/v14040742
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Orthohepevirus C in Archived Human Samples in Germany, 2000–2020

Abstract: Orthohepevirus C1, also known as rat hepatitis E virus (HEV), has been shown to sporadically cause disease in immunocompromised and immunocompetent adults. While routine serological assays vary in reactivity, rat HEV is not detected in routine HEV RT-PCR. Thus, such infections could be either missed or misclassified as conventional HEV (Orthohepevirus A) infections. We conducted a retrospective screening study among serum and plasma samples from patients suspected of having HEV infection, which were archived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In our study, similar to the cited studies, we focused on assessing the circulation of rat HEV and HEV-3 in rats rather than determining rat HEV in swine and other animals. Indeed, the presence of the virus has been investigated in humans in a limited number of countries, including Hong Kong, France, Spain and Germany, and has been detected in patients with acute hepatitis in Hong Kong and Spain and in chronic hepatitis in France [ 5 , 15 , 17 , 45 , 46 ]. The transmission pathway of rat HEV from natural host to human remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, similar to the cited studies, we focused on assessing the circulation of rat HEV and HEV-3 in rats rather than determining rat HEV in swine and other animals. Indeed, the presence of the virus has been investigated in humans in a limited number of countries, including Hong Kong, France, Spain and Germany, and has been detected in patients with acute hepatitis in Hong Kong and Spain and in chronic hepatitis in France [ 5 , 15 , 17 , 45 , 46 ]. The transmission pathway of rat HEV from natural host to human remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid was isolated on an EZ1 ® Advanced XL workstation using the EZ1 Virus Mini Kit v2.0 (Qiagen, Hilden, Germany). Eluted nucleic acid was analyzed by RT-qPCR according to a published protocol [ 13 ]. The HEV-C1 RNA concentration was determined by absolute quantification and expressed as genome copies per mL (c/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In Germany, despite some preliminary serological evidence from a study on forestry workers [ 12 ], no acute PCR-positive individuals have been identified thus far. In particular, a recent study on left-over samples from patients with suspected acute hepatitis E and no detectable HEV RNA found no evidence for infections with rat HEV [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This data includes sixteen patients in Hong Kong, three patients in Spain, one patient in Central Africa, and one patient in France. RHEV initial detection occurred in rats from Germany and Vietnam [3], but no human cases have been found in Germany [15] or Hungary [16] after investigation. In Spain, a comprehensive study conducted by Rivero-Juarez et al revealed the presence of Rocahepevirus ratti infection in three human patients.…”
Section: Human Infections Associated With Rocahepevirus Rattimentioning
confidence: 98%